The Impact of Effective Tax Rate and Cash Effective Tax Rate on the Capital Structure - Khuong, Nguyen Vinh, Dr.; Thao Vy, Tran; Phuong Anh, Nguyen; Thi Anh Hong, Pham; Thi Ngoc Trinh, Bui; Phuong Uyen, Cao (The Indonesian Capital Market Review, 2025)
The study examines the impact of tax avoidance on the capital structure of listed companies on the Vietnam’s stock market. Conducting GLS regression testing and analysis through data of 657 enterprises listed on the two stock exchanges of Hanoi and Ho Chi Minh City in the period from 2015 to 2022. Research results have shown that initially, when businesses carry out tax avoidance, it will reduce the capital structure of the business because the marginal benefits received from tax avoidance are lower than the marginal costs from tax avoidance. However, after businesses carry out tax avoidance and the benefits from this behavior outweigh the costs of tax avoidance, it will help improve capital structure by saving corporate income tax costs. On the other hand, the larger the scale of a business, the more debt it uses, etc. will help the business improve its capital structure. From the results of empirical research and comprehensive evaluation, the thesis has a number of recommendations for business managers and investors. At the same time, identify the remaining limitations of the study and propose future research directions for researchers to contribute to perfecting the theoretical framework on the impact of tax avoidance on corporate capital structure in Vietnam.